Naked mole-rats lack cold sensitivity before and after nerve injury. (September 2020) - Poulson, Sandra J; Aldarraji, Ahmed; Arain, Iqra I; Dziekonski, Natalia; Motlana, Keza; Riley, Rachel; Holmes, Melissa M; Martin, Loren J
Neuropathic pain is a chronic disease state resulting from injury to the nervous system. This type of pain often responds poorly to standard treatments and occasionally may get worse instead of better over time. Patients who experience neuropathic pain report sensitivity to cold and mechanical stimuli. Since the nociceptive system of African naked mole-rats contains unique adaptations that result in insensitivity to some pain types, we investigated whether naked mole-rats may be resilient to sensitivity following nerve injury. Using the spared nerve injury model of neuropathic pain, we showed that sensitivity to mechanical stimuli developed similarly in mice and naked mole-rats. However, naked mole-rats lacked sensitivity to mild cold stimulation after nerve injury, while mice developed robust cold sensitivity. We pursued this response deficit by testing behavior to activators of transient receptor potential (TRP) receptors involved in detecting cold in naïve animals. Following mustard oil, a TRPA1 activator, naked mole-rats responded similarly to mice. Conversely, icilin, a TRPM8 agonist, did not evoke pain behavior in naked mole-rats when compared with mice. Finally, we used RNAscope to probe for TRPA1 and TRPM8 messenger RNA expression in dorsal root ganglia of both species. We found increased TRPA1 messenger RNA, but decreased TRPM8 punctae in naked mole-rats when compared with mice. Our findings likely reflect species differences due to evolutionary environmental responses that are not easily explained by differences in receptor expression between the species.